Kepi ke o chi - Zafiama, Elicio; Segundo, Pedro (Universidad Nacional de Colombia, 2025)
Canto Kepɨ ke o chi (lengua nonuya) e interpretación del canto en pares de reribakui. El canto lo interpreta Elicio Zafiama. El soplo lo ejecutan Pedro Segundo (flauta hembra) y Ginel Dokoe (flauta macho). Esta grabación hace parte de una colección resultante del trabajo de investigación propia del grupo de danza Kaɨ Komuiya Uai (Leticia) sobre flautas y cantos de fakariya.

Kepɨ ke o chi chant (Nonuya language) and performance of the chant in reribakui flutes. The chant is sung by Elicio Zafiama. The interpretation of the flutes is performed by Pedro Segundo (smaller, female flute player) and Ginel Dokoe (larger, male flute player). This recording has This recording is part of a collection resulting from the Kaɨ Komuiya Uai (Leticia) dance group's own research on pan flutes and fakariya chants.
Keywords: 300 - Ciencias sociales::301 - Sociología y antropología; Lengua no escrita; Música indígena; reribakui; pan flutes; flautas de pan; Aerófonos; Tradición oral